2020
DOI: 10.1017/s0007114520000203
|View full text |Cite
|
Sign up to set email alerts
|

The utility of anthopometric indicators to identify cardiovascular risk factors in Vietnamese children

Abstract: BMI, waist circumference (WC) and waist-to-height ratio (WHtR) can be used for discriminating children and adolescents at risk of CVD. However, consensus on how to use these anthropometric indicators is lacking for children and adolescents in Asia. Discrete criteria are promoted internationally, but continuous variables could be used. Data from a survey of 10 949 Vietnamese school-aged children (6–18 years) were used to evaluate the performance of anthropometric indicators to identify elevated blood pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Sample sizes ranged from 152 35 to 32,036 49 participants. WHtR cutoffs ranged between 0.41 20 and 0.59 35 as follows: 10 studies reported cutoffs of 0.41 to 0.45 20,22,24–26,32,42,48,58,60 ; 23 studies reported cutoffs of 0.46 to 0.50 23–30,32–34,36,43–47,51,53–55,57,59 ; and 12 studies reported cutoffs ≥0.51 21,30,31,33,35,37–39,48,52,54,55 . The general characteristics of the studies are depicted in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample sizes ranged from 152 35 to 32,036 49 participants. WHtR cutoffs ranged between 0.41 20 and 0.59 35 as follows: 10 studies reported cutoffs of 0.41 to 0.45 20,22,24–26,32,42,48,58,60 ; 23 studies reported cutoffs of 0.46 to 0.50 23–30,32–34,36,43–47,51,53–55,57,59 ; and 12 studies reported cutoffs ≥0.51 21,30,31,33,35,37–39,48,52,54,55 . The general characteristics of the studies are depicted in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Second, several studies estimated the optimal cutoff using a balance between sensitivity and specificity, while others used the Youden Index. [21][22][23]27,29,33,38,39,41,42,44,45,[47][48][49][50][51]54,57,59 Because the Youden Index maximizes correct classification rates and minimizes incorrect ones, the cutoff produced by this method generates a low frequency of false positives and false negatives. 70 Third, the different WC measurement techniques may cause bias and variability among the included studies, which may be related to the heterogeneity in our pooled analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have compared the predictive utility of BMI, WC and WHtR for common CV risk factors in children and adolescents (25)(26)(27)(28)(29)(30)(54)(55)(56) with most reporting similar performance among these three adiposity indices (25)(26)(27)(28)(29)(30). However, few studies have assessed the performance for identifying LVH and LVG remodeling among children.…”
Section: Discussionmentioning
confidence: 99%